2009
DOI: 10.1111/j.1439-0531.2008.01094.x
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Insemination with a Standard AI Dose in a Sow Pool System

Abstract: The effect of uterine AI with a standard dose of spermatozoa on fertility of the sow was studied in a field trial. The trial involved a sow pool system with 440 sows using AI as the primary method of breeding. Sows were twice a day checked for oestrus symptoms by back pressure test in front of a boar on days 3-6 after weaning. When in standing heat, sows were randomly allocated into either a uterine insemination group (UTER, n = 157) or standard AI group (CONT, n = 169) and bred accordingly using 3 billion spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…Furthermore, farrowing rate and litter size, although reduced with 1 billion sperm, still achieved an 84% farrowing rate and total born litter size of 13.9 pigs [133]. However, the intrauterine method of insemination itself does not improve fertility when higher numbers of sperm (3 billion) are used [138]. Although some studies have shown differences in farrowing rate and litter size with less than 1 billion sperm [139], others report good fertility with only 0.5 billion sperm if insemination occurred within the 24-hour period before ovulation [140].…”
Section: New Insemination Technologiesmentioning
confidence: 85%
“…Furthermore, farrowing rate and litter size, although reduced with 1 billion sperm, still achieved an 84% farrowing rate and total born litter size of 13.9 pigs [133]. However, the intrauterine method of insemination itself does not improve fertility when higher numbers of sperm (3 billion) are used [138]. Although some studies have shown differences in farrowing rate and litter size with less than 1 billion sperm [139], others report good fertility with only 0.5 billion sperm if insemination occurred within the 24-hour period before ovulation [140].…”
Section: New Insemination Technologiesmentioning
confidence: 85%
“…Other work (15) established that the farrowing rate did not differ between CAI using 3.5 x 10 9 spermatozoa in 100 ml and IUI using 2, 1, or 0.5 x 10 9 spermatozoa in 50 ml. Peltoniemi et al (16) concluded that uterine insemination did not have a significant effect on live piglets/litter and farrowing rate. The results from those studies do not necessarily reflect the data from similar procedures on other farms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, deposition of semen in the uterus may be considered more of a physiological method than using the caudal portion of the cervix as the primary site of semen deposition. Generally speaking, intrauterine insemination (post-cervical, semen deposited into the uterine base) and deep intrauterine (semen deposited into uterine horn) have been practiced to allow for a reduction of sperm number per dose, improved fertility or both (Watson and Behan, 2002;Martinez et al, 2002;Peltoniemi et al, 2009). A similar technique was developed to allow transcervical ET (Martinez et al, 2004).…”
Section: Artificial Inseminationmentioning
confidence: 99%